Title to territory/ edited by Malcolm N. Shaw - "Shaw, Malcolm N. (ed.)" (Aldershot, 2005)
The question of territory has always been central to the international legal system. It constitutes the core of the definition of the state, and the state remains the primary element in international law. As such it is tied to the issue of jurisdiction and the extent of the power exercisable by the state. It is also central to the organisation of the international order, for a state-based world community requires rules by which to determine how territory may be allocated to states and the sanctions that may be applied for violation of territorial integrity. Further, as states appear, disappear and re-emerge in a different guise, principles as to the determination of boundaries become critical. The Former Yugoslavia is the most prominent example of this in modern times. This volume consists of numerous important essays describing the role of territory in international law and how the international legal system accepts and regulates the apportionment of territory between states, and regulates boundary questions. The volume is prefaced by a wide-ranging Introduction which lays out the essence of the modern law in this critically important area of international law.
Keywords: "Territory, National"